Penerapan Model Pembelajaran ICARE Untuk Meningkatkan Hasil Belajar Kognitif Siswa Pada Mata Pelajaran Ilmu Pengetahuan Sosial di Madrasah Ibtidaiyah: ICARE Learning Model, Social Studie, Cognitive Learning Outcomes - Qodariyah, Nurul; F. Ramdhan, Dadan; Rahman, Alvin Yanuar (STIT Fatahillah, 2025)
This research is motivated by the existence of problems found in students' cognitive learning outcomes in the subject of Social Sciences in class Ⅳ MI Cibanteng, West Bandung Regency, which shows that there are still students who have not reached the Minimum Completion Criteria (KKM), because there is no effective learning model in the subject of Social Sciences. This study aims to determine: (1) students' cognitive learning outcomes before the implementation of the ICARE learning model, (2) the process of implementing the ICARE learning model in each cycle, and (3) students' cognitive learning outcomes at the end of the cycle after the implementation of the ICARE learning model. This study uses the Classroom Action Research (CAR) method with data collection techniques including observation, testing, and documentation. While data analysis is carried out by calculating the average value, individual learning completion, and classical learning completion, as well as analyzing the results of observations of teacher and student activities. The study's results show an increase in students' cognitive learning outcomes in the subject of Social Sciences when using the ICARE model in each cycle. The research revealed that students' cognitive learning outcomes in the pre-cycle before implementing the ICARE learning model in Social Studies achieved an average score of 62.3, with a classical mastery score of 56%. After implementing the ICARE learning model, the average score increased to 66.1, with a classical mastery score of 64% in Cycle 2. Finally, it reached an average score of 74.7 and a classical mastery score of 78% in Cycle 2. Therefore, it can be concluded that the ICARE learning model can improve students' cognitive learning outcomes in Social Studies in grade Ⅳ at MI Cibanteng, West Bandung Regency.